Work rules! : insights from inside Google that will transform how you live and lead - Bock, Laszlo (Twelve, 2015)
""We spend more time working than doing anything else in life. It's not right that the experience of work should be so demotivating and dehumanizing." So says Laszlo Bock, head of People Operations at the company that transformed how the world interacts with knowledge. This insight is the heart of WORK RULES!, a compelling and surprisingly playful manifesto with the potential to change how we work and live. Drawing on the latest research in behavioral economics and with a profound grasp of human psychology, Bock also provides teaching examples from a range of industries -- including companies that are household names but hideous places to work, and little-known companies that achieve spectacular results by valuing and listening to their employees. Bock takes us inside one of history's most explosively successful businesses to reveal why Google is consistently rated one of the best places to work in the world, distilling 15 years of intensive worker R&D into delightfully counterintuitive principles that are easy to put into action, whether you're a team of one or a team of thousands. Cleaving the knot of conventional management, some lessons from WORK RULES! include: Take away managers' power over employees Learn from your best employees - and your worst Only hire people who are smarter than you are, no matter how long it takes to find them Pay unfairly (it's fairer!) Don't trust your gut: use data to predict and shape the future Default to open: be transparent, and welcome feedback If you're comfortable with the amount of freedom you've given your employees, you haven't gone far enough WORK RULES! shows how to strike a balance between creativity and structure, leading to success you can measure in quality of life as well as market share. Read it to build a better company from within rather than from above; read it to reawaken your joy in what you do. "--